On Discontinuous Dirac Systems with Eigenvalue Dependent Boundary Conditions - Panakhov, Etibar S.; Gulsen, Tuba (Amer Inst Physics, 2015)
In this paper we consider Dirac system with eigenvalue dependent boundary conditions. Then we obtain the existence and uniqueness results of solutions by modifying some known techniques for the investigated problem.
International Conference on Numerical Analysis and Applied Mathematics (ICNAAM) -- SEP 22-28, 2014 -- Rhodes, GREECE
Keywords: Dirac Systems; Transmission Conditions; Discontinuous Boundary-value Problems; Eigenvalues; Eigenvector Functions